The Correlation between Effective Sentence Mastery and Learning Activities with Writing Ability in The Elementary School Students - Reswati, Reswati; Surastina, Surastina; Alfiawati, Riska; Hastomo, Tommy (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
This study aimed to determine the correlation between practical sentence mastery and learning activities with paragraph writing ability. The research method uses the correlation method. Data has collected after all the events in question directly. The technique used in collecting data is a test and questionnaire technique. The research data analysis technique uses a simple and multiple correlation coefficient statistical formulae. Based on the results of research conducted at SD 01 Ujung Gunung Ilir Menggala Tulang Bawang, it is known that learning activities and practical sentence mastery are very significant indicators and determinants of the ability to write paragraphs. It can be seen the results of the study show that the relationship between effective sentence mastery with the ability to write paragraphs can be seen from the value of the regression coefficient of 0.7599 or 75.99%. This value indicates that every 1 per cent increase in learning activity will increase the ability to write paragraphs by 75.99%, assuming other factors do not change. The relationship between effective sentence mastery and paragraph writing ability can be seen from the zero-order correlation coefficient of 0.8299 or 82.99%.